Trends in Therapeutic Communication Skills Research in Indonesian Nursing Education: A Content Analysis - Lameky, Vernando Yanry; Paul, Howard; Mamun, Abdullah Al (PT. Pubsains Nur Cendekia, 2025)
Background: In 21st-century education, developing therapeutic communication skills is a vital goal, especially in nursing education, where effective communication greatly impacts patient outcomes and professional competence. In Indonesia, concern has grown about the gap between theoretical learning and clinical practice in therapeutic communication, which often leads to less effective interactions between nurses, patients, and families. Aims: This highlights the urgent need for research-driven improvements in nursing curricula and teaching methods. Methods: This study conducted a qualitative content analysis of peer-reviewed articles published in Indonesian nursing education journals from 2006 to 2021. The selection process involved identifying and reviewing articles that specifically addressed the development, application, or assessment of therapeutic communication skills in nursing education and practice. Data were analysed through a thematic categorisation approach, focusing on publication trends, research designs, target groups, instruments, and data analysis techniques. Results: The analysis showed that the number of publications focusing on therapeutic communication skills has stayed relatively high in recent years. Quantitative research methods were most common, with descriptive correlational and survey studies leading. Patients were the main research subjects, and among various topics, family-related communication received the most attention. Questionnaires were the most frequently used data collection tools, and correlation tests were the most common data analysis methods. Conclusion: This study suggests that future research should diversify methodologies, including more qualitative approaches (such as ethnographic studies and in-depth interviews) and action research designs, to better capture the real-life dynamics of therapeutic communication. Researchers are also encouraged to provide more detailed information on the validity and reliability of data collection tools and to choose analysis methods that align closely with their research questions and study designs. Improving research on therapeutic communication skills is crucial for advancing nursing education and enhancing the quality of nurse–patient interactions within Indonesia’s healthcare system.